Pengaruh Pemberian Ekstrak Ikan Gabus (Channa Striata) terhadap Penyembuhan Luka Perineum pada Ibu Postpartum di Klinik Pratama Dimens Tinggi Raja: Pengaruh Pemberian Ekstrak Ikan Gabus (Channa Striata) terhadap Penyembuhan Luka Perineum pada Ibu Postpartum di Klinik Pratama Dimens Tinggi Raja - Nurmala Sari; Bayu Larasati; Fitri Andriani; Dwi Feni; Sastrika Handayani (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Perineal rupture remains a prevalent complication of childbirth globally, affecting 40% of mothers in America in 2020, with Asia accounting for 50% of the world's incidence. Locally, data from the Pratama Dimens Tinggi Raja Clinic highlighted the severity, reporting 20 perineal rupture cases out of 31 normal deliveries between January and December 2021. Perineal injury, a tear occurring during labor, is common in both first and subsequent deliveries. Given that snakehead fish contains Albumin, which is vital for accelerating the wound healing process, this study was conducted to examine its therapeutic effect. The research utilized a Quasi-Experiment design with a one-group pretest-posttest approach to measure changes after the intervention: the consumption of snakehead fish extract. The study population included all 30 postpartum mothers at the clinic, from which a sample of 28 respondents was selected via purposive sampling, based on their willingness to consume the extract. Data collection was performed using a checklist sheet. The results strongly indicated a positive effect of the intervention. Among the 28 respondents, 13 individuals (46.4%) showed a 'good' perineal wound healing rate, and a majority of 15 people (53.6%) demonstrated a 'very good' healing rate. Statistical testing, conducted using the independent simple T-Test, confirmed these findings by yielding a p-value of 0.000. As this value is less than 0.05, the study conclusively demonstrates that snakehead fish extract has a significant effect on the acceleration of perineal wound healing in postpartum women.